Incorporate the philosophical thinking of "Wu Wu Guan" into the clinical teaching of medical (Chinese medicine, Mongolian medicine, Western medicine) undergraduates - ZHANG Yu.etc (Journal of Exploration of Vocational Education, 2025)
Since ancient times, Chinese medicine has had a profound cultural heritage. From the very beginning, Chinese medicine has focused on research related to medical humanities, with a particular emphasis on medical methodology and philosophy. On the path of medical development in China, Chinese doctors value and comprehend the "Way of Medicine", and the "Wuwu View" is one of the important philosophical thoughts of medicine proposed by the orthopedic scientist Zhang Yu, which is the "philosophical view and methodology of medicine". The teaching of medical undergraduate students integrates the philosophical thinking of "Wu Wu Guan", promoting innovation in clinical practice and avoiding the path of "mediocre doctors misleading people". This inspires medical undergraduate students to have good medical philosophy thinking and methodology in clinical, scientific research, and teaching aspects of their careers, enabling them to continuously improve and develop innovation in their medical professional field through the combination of "good service and good understanding".